The effect of differences in duration of feeding time on the growth and survival of freshwater pomfret (Colossoma macropomum) larvae - Prameswari Ilsa Tajri Mukti; Netti Aryani; Benny Heltonika; Ade Yulindra; Mira Rahmita Sari; Santi Ramayani (Acta Aquatica: Aquatic Sciences Journal, 2026)
In the fish hatchery business, the availability of silkworm feed is very limited, therefore, it is necessary to use substitute feed in the form of artificial feed produced through a fermentation process using EM4. The study was conducted from February to April 2023 at The Fish Hatchery and Breeding Laboratory of Fishery and Marine Science Faculty of Riau University. The aim of this research was to determine the effect of differences in duration of feeding times on the growth and survival of freshwater pomfret (C. macropomum) larvae, and to determine whether fermented artificial feed can be used as an alternative feed for silk worms. This study used a completely randomized design (CRD) with six treatments and three replications. Treatment used P1 = silk worm feed for 40 days, P2 = commercial feed for 40 days, P3 = fermented commercial feed for 40 days, P4 = silk worm feed for 30 days, and commercial feed fermentation for 10 days, P5 = Feed for silk worms for 20 days and commercial feed fermentation for 20 days, and P6 = Silk worm feed for 10 days, and commercial feed fermentation for 30 days. Larvae were reared for 40 days with a stocking density of 2 individuals/liter. The results showed that the best treatment was obtained in treatment P5 (20 days of silk worms + 20 days of commercial feed fermentation), with an absolute weight growth of 2.11 grams, an absolute length growth of 4.34 cm, a specific growth rate (LPS) of 16.23% / day, and a survival rate of 84.44%. Keywords: Colossoma macropomum; Growth; Replacement Feed; Silkworms; Survival Rate